Biodegradable composite materials

Through the use of seaweed extract, biodegradable fillers, and water made of water, the problem of slow decomposition of existing biological degradation plastics is solved, and the maintenance of composite materials in the environment is quickly decomposed and thermal insulation performance.

CN116157466BActive Publication Date: 2025-01-28SEARO LABS LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180053970.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-26
Filing Date
2021-08-26
Publication Date
2025-01-28
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

Existing biodegradable plastics are slowly decomposed, resulting in long-stayed residence in the environment and difficult to recycle composite materials.

Method used

The composite material composed of seaweed extract, biodegradable fillers, and water. This composite material is quickly completely completely degraded in the environment and can be made by molding process.

Benefits of technology

Realize the insulation performance of composite materials during the service life, and quickly decompose in the environment, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116157466B_ABST
    Figure CN116157466B_ABST
Patent Text Reader

Abstract

The present invention relates to a biodegradable composite material, wherein the composite material comprises a seaweed extract in an amount of 30 to 70 weight %, a biodegradable filler in an amount of 20 to 60 weight %, and water in an amount of 1 to 20 weight %, based on the total weight of the composite material. The present invention also relates to: products, including packaging materials and pottery formed from the composite material; methods for dissolving, composting and biodegrading the composite material or the product; methods for producing the composite material and the product; and methods for reprocessing the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a biodegradable composite material, and also to products, including packaging materials and pottery formed from the composite material, methods for dissolving, composting and biodegrading the composite material or the product, methods for producing the composite material and the product, and methods for reprocessing the composite material. Background Art

[0002] Conventional lightweight insulation products are made from petroleum-based plastics (such as expanded polystyrene) or plant-based bioplastic equivalents. Such materials are lightweight, durable, have good insulating properties, and have high tensile strength. In addition, such materials can have moldability characteristics suitable for large-scale manufacturing. This makes them very suitable for use as packaging materials and cups, for example.

[0003] There is a general desire to move away from petroleum-derived plastics. This is mainly due to the severe environmental impact of such products both during production and during disposal after use. In addition, non-biodegradable bioplastics that cannot be industrially composted or subjected to other specific waste treatment processes tend to break down in nature, producing microplastic materials (microplastics or nanoplastics) that may remain in the environment (with harmful effects) for hundreds of years.

[0004] If left unchecked, plastic pollution is expected to increase fourfold by 2050, with the weight of plastic in the ocean expected to outweigh fish by then. One of the key factors contributing to this growing problem is single-use plastics used as structural stock keeping units [SKUs] (those that can be formed into rigid and load-bearing containers) such as for packaging and disposable cups.

[0005] In light of these issues, there has been a recent trend toward using biodegradable plastics. However, conventional biodegradable plastics, as well as those based on plant-derived materials (so-called bio-based materials), tend to decompose slowly, often taking much longer than the useful life of the product. As a result, even these so-called biodegradable materials, which are claimed to be environmentally friendly, require complex waste management systems or, if improperly discarded, may remain in the environment for a considerable period of time, potentially causing significant ecological harm that could last for decades or even centuries.

[0006] Composite materials are known to be used in the preparation of thermal insulation materials as an alternative to foamed plastics. Composite materials have many advantages over single-component products, the main one being their ability to tailor and modify properties based on the choice and proportion of the ingredients. However, composite materials are often difficult to recycle, as the components often require different waste disposal processes, and separating the components is often tricky.

[0007] Some composite materials serve as lining or coating of heat-insulating materials such as corrugated board, and an example is disposable coffee cup.Other composite materials use filler particulate materials and binding agents.The composite material formed by biodegradable filler and / or natural organic filler (such as cork, tea, coffee particles, sawdust, paper, hemp fiber, hay, straw, dry granular food waste etc.) and suitable binding agent or adhesive is known, for example, cork particles are referred to as polymerized cork, and these cork particles are optionally mixed with particles of other materials, and are kept together by binding agents to form sheet or block materials.But the binding agents in these composite materials are usually gum-based or other petroleum derivatives, and it exists the same environmental hazards as other petroleum-derived products.

[0008] The term "biodegradable composite material" includes various mixed materials of at least two phases, wherein the filler or the matrix or both must be selected from biodegradable sources. However, encapsulating a biodegradable filler in a non-biodegradable binder does not necessarily result in a biodegradable material. To ensure rapid mechanical and / or chemical decomposition of the material, the binder holding the filler together must decompose rapidly to exploit the inherent biodegradability of the filler material.

[0009] Cork, as an example of a biodegradable filler, is a highly sustainable natural material that comes from the outer bark of the cork oak tree (specific name: Quercus suber), which is a renewable resource and is harvested regularly from living trees (no faster than every 5 years). Cork has unique properties such as lightness and buoyancy, thermal insulation, high temperature resistance, and is hypoallergenic and impermeable to liquids and gases.

[0010] Cork is used in multiple industries such as consumer goods, automotive, power industry, construction, flooring, panels and composites. Cork can be used in its natural state, however, 99% of cork products are made from cork composites; cork particles are combined with petroleum-based plastic binders (such as ABS, PVC, PE), thermoplastic elastomers (such as rubber) or bioplastics (such as PLA). However, these composites are not biodegradable in nature and will cause environmental damage that will last for centuries.

[0011] Polymerizing cork using cork particle filler and polyurethane glue is known, see for example US Pat. No. 5,317,047. Although cork is a natural wood product and is inherently biodegradable, the composite is not biodegradable due to the non-biodegradability of the binder.

[0012] Cork composites using a binder comprising a biodegradable material have been described. WO2016020361 describes the use of a bio-based plastic as a binder. However, the binder is said to meet the standards set out in ASTM 6400, which requires that the material be aerobically compostable in industrial and municipal compounding facilities. The use of the composite material described is for cork bottle stoppers, and this therefore implies that it is a corollary that the material will not biodegrade easily or quickly when in contact with water or moisture.

[0013] Sawdust is another example of a biodegradable filler that is clean, bulk, cheap and readily available as a waste byproduct of woodworking operations such as planing, milling drilling, sanding and sawing. The use of sawdust provides a new use for recycled wood fibers, thereby reducing waste in landfills. Sawdust has been used as a filler with different petroleum-derived polymers such as polyethylene [Horta et al., Procedia Manufacturing, 12, 2017, pp. 221-229; and Kusuktham, Siliconidia 11(4), 2019, pp. 1997-2013], polystyrene [Latthe et al., Mater. Chem. Phys. 2020, pp. 122634; Nasution et al., J. Eng., 15(2), 2019, pp. 17-29; Bruscato et al., J. Clean Prod., 234, 2019, pp. 225-232], polypropylene [Fernanda et al., Polym. Test., 19, 2000, pp. 625-629], natural rubber [Homkhiew et al., Int. J. Polym. Sci., 2018], ethylene-propylene-polymer rubber [Craciun et al., Polymers, 12(1), 2020, 215]. Sawdust has not been previously used as a biodegradable material in super biodegradable composites or used with seaweed-based binders.

[0014] Tea and coffee grounds as by-products of the hospitality industry are further examples of biodegradable fillers which have the combined advantage of being biodegradable once the composite material begins to break down, and also utilise waste that would otherwise end up in landfill.

[0015] Hemp, paper, hay and straw are additional well-known fillers used in other composite materials.

[0016] There remains a need to replace insulating plastics and bioplastics in products with environmentally friendly materials that rapidly and completely biodegrade in the environment or in waste streams, with no or minimal harm to the environment or ecosystem. Such replacements may suitably utilize biodegradable binders for biodegradable insulating filler materials, such as cork. Suitably, the biodegradation time of the insulating material will better match the period of use (particularly, single use) while still providing at least one of the desired material properties of conventional insulating plastics described above. Summary of the invention

[0017] In a first aspect, the present invention provides a composite material, the composite material comprising a seaweed extract in an amount of 30 to 70 wt %, a biodegradable filler in an amount of 20 to 60 wt % and water in an amount of 1 to 20 wt %, based on the total weight of the composite material. Suitably, the seaweed extract is present in an amount of 40 to 60 wt %, the biodegradable filler is present in an amount of 30 to 50 wt %, and the water is present in an amount of 2 to 15 wt %.

[0018] In an embodiment, the composite material consists essentially of seaweed extract, biodegradable filler and water. Suitably, the composite material consists of seaweed extract, biodegradable filler and water. Suitably, the weight percentages of seaweed extract, biodegradable filler and water add up to 100 weight % of the total weight of the composite material.

[0019] In an embodiment, the seaweed extract is selected from the group consisting of: carrageenan; agar; alginate; and mixtures thereof. Suitably, the seaweed extract is carrageenan. Suitably, the carrageenan is kappa carrageenan.

[0020] In an embodiment, the composite material does not contain one or more of the group consisting of: starch; iota carrageenan; agar; alginate; and chitosan.

[0021] In an embodiment, the biodegradable filler is selected from the group consisting of cork, tea leaves, coffee particles, sawdust, paper, hemp, hay, straw, dry granulated food waste, dry granulated plant seeds, dry granulated fruit and vegetable peels or rinds, and mixtures thereof. Suitably, the biodegradable filler is cork.

[0022] In an embodiment, the composite material further comprises one or more additives. Suitably, the one or more additives are present in no more than 40 wt % of the total weight of the composite material. Suitably, the one or more additives are selected from the group consisting of: salt, such as sea salt, table salt, sodium chloride, potassium chloride; and glycerol.

[0023] In an embodiment, the composite material is fully biodegradable. Suitably, the seaweed extract of the composite material:

[0024] a) completely biodegradable in less than six months in an external non-industrial environment;

[0025] b) is completely biodegradable in an aerobic and / or anaerobic atmosphere; and / or

[0026] c) Completely compostable in a home compost pile in less than six months

[0027] d) Completely biodegrades in the ocean in less than 6 months.

[0028] In an embodiment, the composite material is moldable.

[0029] In a second aspect, the present invention provides a product formed from the composite material of the first aspect. Suitably, the product has a shape selected from the group consisting of: a plate; a planar sheet; a regular sphere; an irregular sphere; a regular spheroid; an irregular spheroid; a regular cube; an irregular cube; a regular cuboid; an irregular cuboid; a regular ellipsoid; an irregular ellipsoid; a regular cylinder; an irregular cylinder; a regular cone; an irregular cone; a regular prism; an irregular prism; a regular pyramid; an irregular pyramid; a shell-like, clam-like, or a shape having an internal void or hollow, and any combination thereof.

[0030] In a third aspect, the present invention provides a method for producing the composite material of the first aspect, the method comprising the following steps:

[0031] a) contacting the seaweed extract with water to form a seaweed extract hydrogel,

[0032] b) mixing the seaweed extract hydrogel with a biodegradable filler to form a mixture, and

[0033] c) drying the mixture to form the composite material.

[0034] Suitably, the biodegradable filler is cork. In an embodiment, step (a) comprises heating a mixture of seaweed extract in water to a temperature in the range of about 70°C to about 100°C to form a seaweed extract hydrogel.

[0035] In an embodiment, the method comprises steps (a) to (c) of the method for producing a composite material of the third aspect, and the following additional step between steps (b) and (c): moulding the mixture into the shape of a product or a three-dimensional form.

[0036] In a fourth aspect, the present invention provides a method for reprocessing a product, the method comprising producing the product by the method of the third aspect, wherein the method further comprises:

[0037] f) softening or melting the product by contacting the product with water or steam to provide a softened product;

[0038] g) further manipulating the softened product to provide a reworked product, wherein the reworked product has a different shape than the product;

[0039] h) drying the reprocessed product to provide a dried reprocessed product.

[0040] In a fifth aspect, the present invention provides a method for industrial biodegradation of the composite material of the first aspect or the product of the second aspect, the method comprising the step of exposing the composite material or the product to conditions in which the biodegradation rate is increased.

[0041] In a sixth aspect, the present invention provides a method of composting the composition of the first aspect or the product of the second aspect, the method comprising the steps of: exposing the composition or product to conditions in which the composition or product degrades to form compost or a material suitable for use in compost or as a soil additive for use as a soil fertilizer. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] One or more embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings, in which:

[0043] Figure 1 An example of a product formed from a composite material of the present invention (Composite 1; Table 1) having a kappa carrageenan / cork / water ratio of 51 / 40 / 9 by weight, based on the total weight of the composition, is shown.

[0044] Figure 2 One example of a product formed from a composite material of the present invention (Composite 2; Table 1) having a kappa carrageenan / cork / water ratio of 50 / 41 / 9 by weight, based on the total weight of the composition, is shown.

[0045] Figure 3 One example of a product formed from a composite material of the present invention (Composite 3; Table 1) having a kappa carrageenan / cork / water ratio of 49 / 42 / 8 weight % based on the total weight of the composition is shown.

[0046] Figure 4An example of a product formed from a composite material of the invention (Composite 4; Table 1) having agar / cork / water in a weight % ratio of 52 / 40 / 8, based on the total weight of the composition is shown.

[0047] Figure 5 A comparison of two composite materials according to the invention is shown, the two composite materials differing in the size of the cork particles used. (a) shows a composite material having a weight % ratio of 49 / 42 / 8 of kappa carrageenan / cork / water (composite 5; Table 1), wherein the average diameter of the cork particles is 0.2 mm; (b) shows a composite material having a weight % ratio of 51 / 40 / 9 of kappa carrageenan / cork / water (composite 1; Table 1), wherein the average diameter of the cork particles is 0.5 mm, all weight percentages being based on the total weight of the composition.

[0048] Figure 6 Shown is a composition according to the invention comprising sawdust as biodegradable filler (composite material 9; Table 1), which was cast on a mould and dried.

[0049] Figure 7 Shown is a composition according to the invention comprising tea leaves as a biodegradable filler (composite 10; Table 1), which was cast on a mould and dried.

[0050] Figure 8 Shown is a composition according to the invention comprising coffee grounds as a biodegradable filler (composite 11; Table 1), cast on a mould and dried.

[0051] definition

[0052] For convenience, before further describing the present disclosure, certain terms used in the specification and examples are described below. These definitions should be interpreted in accordance with the remainder of the present disclosure and understood by those skilled in the art. The terms used herein have meanings recognized and known by those skilled in the art, but, for convenience and completeness, specific terms and their meanings are set forth below.

[0053] The articles "a," "an," and "the" refer to one or to more than one (ie, to at least one) of the grammatical object of the article.

[0054] As used herein, the term "comprising / including" means that any listed elements must be included and other elements may also be optionally included. "Substantially consisting of..." means that any listed elements must be included, excluding elements that have a substantial impact on the basic and novel characteristics of the listed elements, and other elements may be optionally included. "Consisting of..." means that all other elements except the listed elements are excluded. Embodiments defined by each of these terms are within the scope of the present invention. When used for certain components of a composite material, the term "comprising" should be understood to provide a clear literal basis for the terms "substantially consisting of (those same components)" and "consisting of (those same components)".

[0055] As used herein, the term "biodegradable" means capable of chemical and / or physical decomposition in nature and / or by the action of organisms. The term is used herein to refer to a composite material or a component in a composite material that is generally naturally decomposed into harmless components in water or an aqueous or humid environment by the action of microorganisms such as bacteria or fungi. Composite materials can meet European standard EN 13432, or more generally, 90% of the material is decomposed into particle fragments not exceeding 2 mm in size after twelve weeks and biodegrades at least 90% after six months (laboratory test method EN 14046). As defined herein, the term "super biodegradable" can be used to refer to a material with a particularly fast biodegradation rate, for example, in a natural, non-modified environment or waste stream in less than 6 months, suitably less than 3 months, completely biodegraded. In this context, the term "natural" or "natural" refers to a non-industrial environment and / or an environment that has not been modified to promote biodegradation, such as an open air or a household compost pile.

[0056] As used herein, the term "compostable" means capable of decomposing in nature and / or by the action of organisms for use as compost. Suitably, the term "compostable" may be used to refer to a composite material or product that can be accepted for addition to a composting site. The term "home compostable" may be used to refer to a composite material or product that can be composted in a domestic environment, for example, added to a compost pile established in a home garden. The term may refer to plastics that meet the following specifications: Australian Specification AS 5810 "Biodegradable plastics-biodegradable plastics suitable for homecomposting" (biodegradable plastics-biodegradable plastics suitable for home composting); Belgian certified OK Compost Home Certification Scheme, which requires at least 90% degradation within 12 months at ambient temperature; and / or the French standard NF T 51-800 "Plastics-Specifications for plastics suitable for home composting". The term "industrially compostable" may be used to refer to composite materials or products that can accept their addition to an industrial composting waste stream. An industrial composting waste stream may, for example, involve an active composting phase followed by curing. The active composting phase typically lasts at least 21 days, and during this time the temperature of the compost pile is maintained at about 50°C to 60°C. For hygienic purposes, the temperature may be kept above 60°C for at least one week to eliminate pathogenic microorganisms. During the curing phase, the decomposition rate slows down as humus is synthesized, and the temperature drops to <40°C.

[0057] As used herein, the term "non-hazardous" means non-toxic or poses no risk to humans, animals or the environment. In terms of a compound, non-hazardous may mean complying with any one or more of the following: EC Regulation No. 1907 / 2006, EC Regulation No. 1272 / 2008, REACH Directive 1999 / 45 / EC, No. 76 / 769 / EEC, European Council Directives 793 / 93 and 91 / 155 / EEC, 93 / 67 / EEC or 67 / 548 / EEC; or reaching Class IV toxicity (practically non-toxic and non-irritating) or its equivalent under Title 40 of the U.S. Code of Federal Regulations (156.62).

[0058] As used herein, the term "bioplastic" means plastic materials produced from renewable biomass sources such as vegetable fats and oils, corn starch, straw, wood chips, sawdust, recycled food waste, etc. Bioplastics can be made from agricultural byproducts. Bioplastics indicate that the source of the material from which the plastic is made is biological. Although some bioplastics may be biodegradable, the term "bioplastic" does not imply that the material is biodegradable.

[0059] The term "cork" as used herein means a natural material obtained from the bark or trunk of a cork oak tree (species name: Quercus suber).

[0060] As used herein, the term "seaweed" is a general term referring to a group of multicellular algae typically found in or near oceans or freshwater bodies. Types of seaweed include Rhodophyta (red), Phaeophyta (Brown) and Chlorophyta (Green) Large algae. Many brown algae are simply called kelp.

[0061] As used herein, the term "seaweed extract" refers to a separated or isolated seaweed component or component. Suitably, the separation or isolation method is by chemical or physical extraction (i.e., gel pressing or precipitation in alcohol and alkaline hydrolysis). For example, a seaweed extract can be obtained by crushing the seaweed plant or part thereof, followed by filtration to remove solid seaweed residual material; or alternatively, washing the seaweed with a suitable solvent (e.g., alkaline aqueous solution), and collecting the desired extract as the remaining insoluble matter or a portion thereof. The extract may be subjected to further purification / separation steps. Examples of seaweed extracts according to the meaning herein are the extracts carrageenan, agar and alginate, suitably carrageenan.

[0062] As used herein, the term "carrageenan" refers to a class of linear sulfated polysaccharides extracted from red seaweed. There are three main types of carrageenan, which differ in their degree of sulfation. Kappa carrageenan has one sulfate group in each disaccharide, iota carrageenan has two sulfate groups, and lambda carrageenan has three sulfate groups.

[0063] As used herein, the term "thermal insulation" means having low thermal conductivity. The thermal conductivity of a material is a measure of its ability to conduct heat. It is usually denoted by k, λ, or κ. Materials with low thermal conductivity have a lower rate of heat transfer than materials with high thermal conductivity. For example, metals generally have high thermal conductivity and conduct heat very efficiently, while expanded polystyrene (or ) and other insulating materials are the opposite. Thermal conductivity is usually measured using Fourier's law of heat conduction. Calculate, where q is the heat flux, k is the thermal conductivity, and is the temperature gradient.

[0064] As used herein, the term "binder" refers to a matrix in a composite material that holds or binds fillers or aggregates together. The binder may be all materials present in the composite material other than fillers, or the binder may refer to a material that binds the fillers together, but other materials may also be present in the composite material or mixed with the binder to provide a composite material.

[0065] As used herein, the term "filler material" or simply "filler" or "bioaggregate" refers to particles added to a resin or binder to improve specific properties, make the product cheaper, or both. "Natural organic fillers" are fillers derived from natural sources such as plants or animals. "Biodegradable fillers" are fillers that are capable of biodegradation (as defined elsewhere herein) in composite materials. Examples of biodegradable fillers can be cork (e.g., cork particles of various sizes), tea leaves, coffee particles, sawdust, hemp fibers, hay, straw, dry granular food waste, etc.

[0066] As used herein, the term "biodegradable composite material" refers to any mixed material having at least two phases, wherein either the filler or the matrix (binder) or both must be selected from biodegradable sources. Suitably, a biodegradable composite material means that both the filler and the matrix (binder) must be selected from biodegradable sources. DETAILED DESCRIPTION

[0067] The present invention relates to a biodegradable insulation composite material that completely and rapidly decomposes (super biodegradable) in the environment (particularly in various aqueous or other non-dry environments) or in waste streams or in compost, but still retains one, more or all of the benefits of petroleum-based plastic or plant-based bioplastic insulation materials during its useful life.

[0068] The insulating composite material of the present invention generally comprises seaweed extract and biodegradable filler or bioaggregate (suitably cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dry granulated food waste, granulated plant seeds, dry granulated fruit and vegetable peels / peels. Suitable biodegradable fillers are cork, suitably cork particles. The composite material may further comprise water. Suitably, the composite material comprises seaweed extract, biodegradable filler and water. Suitably, the composite material consists essentially of seaweed extract, biodegradable filler and water. Suitably, the composite material consists of seaweed extract, biodegradable filler and water.

[0069] In an embodiment, the seaweed extract may be carrageenan, agar or a mixture thereof. Carrageenan compounds and the agar family are well known in the fields of food, pharmaceuticals and personal care products; however, they are chemically different. Carrageenan contains repeating units of β-D-galactose-α-D-galactose, while agar contains repeating β-D-galactose-α-L-galactose. Suitably, the seaweed extract used in the composite material of the present invention is carrageenan. More suitably, the carrageenan may be a kappa carrageenan.

[0070] It is contemplated that any seaweed extract may be used in the present invention. However, as expected, while carrageenan, agar and other seaweed extracts have a common source (seaweed) and related chemical structures, each substance has different properties when formed into a super biodegradable alternative material. For example, carrageenan (particularly kappa carrageenan) exhibits surprisingly beneficial mechanical material properties when mixed with a biodegradable filler (e.g., cork) (as in the present invention) compared to agar and other seaweed extracts.

[0071] In an embodiment, the biodegradable filler material can be obtained from a natural organic material or from a mixture of natural organic materials (usually plant-derived). Suitably, the biodegradable filler material is cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dry granular food waste, granular plant seeds, dry granular fruit and vegetable peels / peels. Suitably, the biodegradable filler is cork. Suitably, the biodegradable filler can be present in the composite material as cork (suitably cork particles or microparticles or powder).

[0072] In an embodiment, the filler material may have a specific particle size selected for the physical or mechanical properties of the composite material or influenced by the commercial availability of the filler material. For example, the cork particles according to the present disclosure particularly include particles having the following particle size measured according to ISO 2030: 1990: in the range of from 1 μm to 2 cm, particularly in the range of from 1 μm to 1.5 cm, more particularly in the range of from 0.1 cm to 1.2 cm, even more particularly in the range of from 0.1 cm to 1 cm, yet more particularly in the range of 0.1 cm to 0.9 cm, even more particularly in the range of 0.2 cm to 0.8 cm, even more particularly in the range of 0.2 cm to 0.5 cm.

[0073] In an embodiment, the insulating composite material comprises only seaweed extract (such as carrageenan), biodegradable filler (suitably cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dry granulated food waste, granulated plant seeds, dry granulated fruit and vegetable peels / peels, suitably cork, suitably cork particles), and the remainder of the composite material is water. In other words and as defined herein, the composite material may consist of seaweed extract and biodegradable filler, seaweed extract and biodegradable filler, and water. In other words, the weight percentages of these components may add up to 100 weight % based on the total weight of the insulating composite material.

[0074] In embodiments, it is contemplated that other additives may be included in the composite material that may provide one or more benefits without adversely affecting the overall properties of the composite material. In other words and as defined herein, the composite material may consist essentially of seaweed extract and biodegradable filler (suitably cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dried granulated food waste, granulated plant seeds, dried granulated fruit and vegetable peels / peels, suitably cork), or consist of seaweed extract and biodegradable filler (suitably cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dried granulated food waste, granulated plant seeds, dried granulated fruit and vegetable peels / peels, suitably cork) and water. The term "minor additive" or "additive" is intended to refer to additives other than seaweed extract and biodegradable filler, which may be present in the composite material in an amount of 40% by weight or less. Suitably, less than 35 wt%, 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, 5 wt%, 2 wt%, 1 wt%. All weight percentages are based on the total weight of the composite material. In other words, the weight percentages of seaweed extract, biodegradable filler (suitably cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dry granulated food waste, granulated plant seeds, dry granulated fruit and vegetable peels / peels, suitably cork), water and one or more additives may add up to 100 wt% based on the total weight of the composite material.

[0075] The additive or secondary additive may be, but is not limited to, an inorganic salt such as sea salt, table salt, potassium chloride or calcium chloride; hydrophilic colloid, xanthan gum, gum arabic, MC, CMC, HPMC; calcium carbonate; glycerine; applesauce; starch; montmorillonite (MMT); vegetable oil; cinnamon bark oil; soybean oil; glycerol; silver nanoparticles; grapefruit seed extract; Zataria multiflora essential oil; nanoclay or clay mineral; polyethylene glycol (PEG); chitin; arabinoxylan; banana powder; gelatin; titanium oxide nanoparticles. Alternatively, in an embodiment, the composite material of the present invention and the product formed therefrom may not contain any secondary additives (including but not limited to one or more of those listed above).

[0076] In an embodiment, the composite material may include a salt, more suitably an alkali metal salt or an alkaline earth metal salt, even more suitably a lithium salt, a sodium salt, a calcium salt or a potassium salt. Most suitably, the composite material may include a potassium salt. In an embodiment, the potassium salt is potassium chloride. Suitably, the composite material may include a salt in an amount in the range of 0.1 wt % to 5 wt %, more suitably in the range of 0.5 wt % to 3 wt %, even more suitably in the range of 0.5 wt % to 1.5 wt %. Suitably, the salt may be present in the composite material in an amount of at least 0.1 wt %, 0.2 wt %, 0.3 wt %, 0.4 wt %, 0.5 wt %, 0.6 wt %, 0.7 wt %, 0.8 wt %, 0.9 wt %, 1.0 wt %, 2.0 wt %, 3.0 wt %, 4.0 wt % or more. Suitably, the salt may be present in the composite material in an amount of up to 5.0 wt%, 4.0 wt%, 3.0 wt%, 2.0 wt%, 1.9 wt%, 1.8 wt%, 1.7 wt%, 1.6 wt%, 1.5 wt% or less based on the total weight of the composite material; all weight percentages are based on the total weight of the composite material. Without wishing to be bound by theory, it is believed that the inclusion of such salts may increase the rigidity of the resulting composite material and products formed therefrom.

[0077] In an embodiment, the composite material may include a vegetable oil or an extract or derivative thereof, such as glycerol. More suitably, the composite material may include glycerol in an amount ranging from 0.1 wt % to 40 wt %, even more suitably ranging from 10 wt % to 35 wt %, more particularly ranging from 25 wt % to 35 wt %, all weight percentages being based on the total weight of the composite material. Without wishing to be bound by theory, it is believed that the inclusion of a vegetable oil, such as glycerol, may increase the flexibility of the resulting product.

[0078] In an embodiment, composite material can comprise the seaweed extract of the amount of 40 % by weight to 95 % by weight, suitably 50 % by weight to 95 % by weight, more suitably 50 % by weight to 70 % by weight. Suitably, composite material can comprise the seaweed extract of the amount of at least 40 % by weight, 45 % by weight, 50 % by weight, 55 % by weight, 60 % by weight, 65 % by weight, 70 % by weight, 75 % by weight, 80 % by weight, 85 % by weight or 90 % by weight. Suitably, composite material can comprise the seaweed extract of the amount of at most 95 % by weight, 90 % by weight, 85 % by weight, 80 % by weight, 75 % by weight, 70 % by weight, 65 % by weight, 60 % by weight, 55 % by weight, 50 % by weight or 45 % by weight. All percentages by weight are all based on the gross weight of composite material.

[0079] In an embodiment, the composite material may include a biodegradable filler (suitably cork, tea leaves, coffee particles, sawdust, hemp fiber, hay, straw, dry granular food waste, granular plant seeds, dry granular fruit and vegetable peels / peels, suitably cork) in an amount of 5% to 50% by weight, more suitably 20% to 50% by weight or 30% to 50% by weight. Suitably, the composite material may include a biodegradable filler in an amount of at least 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45% by weight. Suitably, the composite material may include a biodegradable filler in an amount of up to 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15% or 10% by weight. All percentages by weight are based on the total weight of the composite material.

[0080] In an embodiment, the composite material may include 1 wt % to 20 wt %, even more particularly 2 wt % to 15 wt % water, all weight percentages being based on the total weight of the composite material. Suitably, the composite material may include at least 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt % or 14 wt % water. Suitably, the composite material may include up to 15 wt %, 14 wt %, 13 wt %, 12 wt %, 11 wt %, 10 wt %, 9 wt %, 8 wt %, 7 wt %, 6 wt %, 5 wt %, 4 wt % or 3 wt % water. All weight percentages are based on the total weight of the composite material.

[0081] In a specific embodiment of the composite material according to the present invention, the composite material may comprise 50 wt% to 90 wt% or suitably 45 wt% to 55 wt% of kappa carrageenan (in an embodiment, based on the data provided, at least 48 wt% of seaweed extract is required, but better results can be obtained with 50 wt% to 60 wt% of seaweed extract), 10 wt% to 60 wt% or suitably 30 wt% to 45 wt% of cork particles (in an embodiment, based on the data provided, up to 43 wt% of cork is required, but the percentage of cork can be as low as 10 wt%), 4 wt% to 25 wt% or suitably 6 wt% to 10 wt% of water. All weight percentages are based on the total weight of the composite material. In an embodiment, the weight percentages of kappa carrageenan, cork and water can add up to 100 wt% based on the total weight of the composite material.

[0082] The thermal insulation composite material of the present invention is hygroscopic, that is, the composite material absorbs water. Without wishing to be bound by theory, it is believed that the excellent biodegradability or super biodegradability of the composite material of the present invention is at least partially due to its ability to absorb water and the fact that the main component of the composite material is a natural food source, which promotes and facilitates the growth of microorganisms such as bacteria or fungi on the composite material, thereby causing its biodegradation.

[0083] The seaweed binder of the thermal insulation composite of the present invention can absorb large amounts of water without losing integrity or leaking or cracking. For example, the seaweed binder can absorb about 10 to 13 grams of water per gram of material, resulting in a weight change of about 1,000 to 1,300 percent when the binder is exposed to water.

[0084] A particular advantage of the composite material of the present invention is that the material is thermally insulating, i.e. has a low thermal conductivity. Low thermal conductivity is important in various applications including thermal insulation, for example as a container for warm beverages, or as a packaging material where the contents are intended to be kept at a temperature above or below the ambient temperature. It is envisaged that the composite material of the present invention is also electrically insulating, at least to some extent.

[0085] Another advantage of the composite material of the present invention is that by incorporating fillers with inherently low density (e.g. cork), the composite material is lighter per unit volume, i.e. has a low density. This may be particularly advantageous in applications where weight reduction is required (such as large containers) or in applications where buoyancy is required.

[0086] Furthermore, the tendency of the composite materials of the invention to absorb water upon contact promotes microbial growth and thereby promotes rapid (<2 months) and significant biodegradation when in contact with water in the air, e.g., humidity or precipitation (urban roadside type environments), in compost, in waste streams, or in sewers, oceans or rivers. Furthermore, and without wishing to be bound by theory, it is conceivable that the ability of the material to absorb water in this manner and then release it again by evaporation is a factor in its rapid physical degradation, due to the stresses generated by the material undergoing cycles of wetting and drying causing collapse and fragmentation of the material structure.

[0087] It is also expected that at least a portion of the composite material of the present invention is also capable of decomposing and / or dissolving in the digestive tract fluids. Therefore, in view of its harmless and food-safe components, it is conceivable that the composite material is harmless for human and / or animal consumption, that is, the material is edible at least in principle. Since seaweed extracts, especially carrageenan and agar, for example, are common additives in many foods, a feature of the composite material of the present invention is that the composite material is food-safe. Since the composite material contains cork, sawdust, etc., some components may not be digestible by all animals.

[0088] It is envisioned that the seaweed binder of the composite material is soluble in water at a temperature of at least 50° C., more particularly at least 75° C., and even more particularly at least 85° C. The length of time required for dissolution depends at least in part on the form or shape and thickness of the material, with complete dissolution expected within 1 hour at 85° C. under continuous mixing conditions for a sheet material having a wall thickness of approximately 1 mm.

[0089] Although the composite material of the present invention or the product formed therefrom exhibits surprisingly beneficial properties in terms of biodegradability in the environment or in water, when stored under relative humidity conditions of 80% or less, the composite material or the product formed therefrom may exhibit a shelf life of up to 3 years, more particularly 2 to 3 years, before use.

[0090] On the other hand, the present invention relates to a product comprising the above-mentioned biodegradable thermal insulation composite material or formed therefrom. In an embodiment, the product can be a shaped article, such as a sheet or a film, or the product can be a three-dimensional shaped article. Suitably, the three-dimensional shaped article can generally be shaped as a plate or a planar sheet, or shaped as a regular or irregular sphere or spheroid, a cube or a cuboid, an ellipsoid, a cylinder, a cone, a prism, a pyramid or a combination thereof. Suitably, the product can be a packaging material. Suitably, the packaging material can be a container or a part thereof. Suitably, the container or a part thereof can be a cup, a tray, a flat basket, a clamshell, a box, a bottle, a tube or a lid. Suitably, the container or a part thereof can be a packaging material, in particular a packaging material for perishable items such as food. In addition to packaging, the present invention also relates to other disposable consumer products formed by the above-mentioned composite material, such as a straw, a cup, a plate or a food tray. The surprising structural rigidity and other material properties of the composite material make it particularly suitable for structural three-dimensional products with thin walls, such as packaging materials and cups.

[0091] In an embodiment, the thickness of the product may be suitable for this purpose. Suitably, the product of the present invention, for example when the product is a biodegradable packaging material or a cup, may have a thickness (the minimum distance between the two surfaces of the product) of 10 mm or less (due to the cork particle size, the thickness of the material may increase by up to 10 mm). Suitably, the product may have a thickness of at most 9 mm, 8 mm, 7 mm, 6 mm, 5 mm, 4 mm, 3.5 mm, 3.0 mm, 2.5 mm, 2.0 mm, 1.5 mm, 1.0 mm, 0.5 mm, 0.4 mm, 0.3 mm or 0.2 mm or less. Suitably, the product may have a thickness of at least 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1.0 mm, 1.5 mm, 2 mm or more. Each of these thicknesses may be used in structural and load-bearing three-dimensional products.

[0092] In an embodiment, the insulating composite material of the present invention forms a resilient self-supporting structure when molded and subsequently dried, which is capable of supporting a load and / or holding a beverage, having properties similar to petroleum-based plastics or bio-based composites. The rigidity and high tensile strength properties of the composite material of the present invention allow the material to be used to form "structural packaging", that is, packaging or products that form a three-dimensional load-bearing structure without external support of the structure, as well as liners or coatings supported by other structures or products. Without wishing to be bound by theory, it is believed that the seaweed extract, suitably carrageenan, particularly kappa carrageenan, provides surprisingly beneficial properties to the composite material in terms of structure and load-bearing.

[0093] The composite material of the present invention or the product formed therefrom can accept printing media, such as water-based or oil-based inks. The composite material of the present invention and the product formed therefrom can be suitably molded to show the embossed details present on the mold. The structural rigidity of the product is similar to that of petroleum-based plastic or bioplastic composite materials, which means that it is expected that the product of the present invention will be able to be used in current printing machinery without modification.

[0094] The products of the present invention, such as packaging materials, may exhibit useful oxygen barrier properties. This may mean that the packaging material will keep the contained items fresher for longer and extend their shelf life.

[0095] In another surprising benefit of the present invention, it has been found that food packaging made from or comprising the insulating composite material of the present invention can extend the shelf life of the food contained therein (suitably fresh food, vegetables or dairy products such as cheese) compared to traditional petroleum-based plastics (such as polyethylene terephthalate (PET)) or bioplastics (such as PLA). The hygroscopicity of the composite material means that any ambient moisture within the package is absorbed by the composite material and retained, meaning that the environment in which the food is stored becomes less suitable for microbial growth, which typically leads to mold growth and decay. This, together with the oxygen barrier properties of the composite material, delays the deterioration of the food within the package, thereby extending the shelf life of the food.

[0096] In an embodiment, the shelf life (defined as the length of time that an item remains suitable for consumption or sale) of agricultural products or perishable items contained in a product or structured stock keeping unit (SKU) can be extended by at least 10% at a given temperature. Suitably, the shelf life can be extended by at least 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 200%, 300%, 400%, 500% or more.

[0097] In another aspect, the present invention relates to a method for preparing a thermal insulation composite material as defined above, the method comprising the following steps:

[0098] (a) contacting a seaweed extract with water or other suitable polar solvent to form a seaweed extract hydrogel;

[0099] (b) mixing the seaweed extract hydrogel with a biodegradable filler to form a mixture;

[0100] (c) drying the mixture to form a composite material.

[0101] The seaweed extract in step (a) and / or the biodegradable filler in step (b) may be as defined elsewhere herein. Suitably, the seaweed extract is kappa carrageenan. Suitably, the biodegradable filler may be any particulate material defined as biodegradable. Suitably, the biodegradable filler is selected from the group consisting of: cork; dry tea leaves; coffee particles; sawdust; hemp fibers; hay, straw, dry granulated food waste, granulated plant seeds, dry granulated fruit and vegetable peels or skins, more suitably cork particles.

[0102] Except water, suitable polar solvent in step (a) can be any polar solvent that can form suitable hydrogel with seaweed extract. Suitably, polar solvent has boiling point that allows to dry preparation after molding. Suitably, this solvent is harmless and does not damage the environment. Polar solvent in this context can include but not limited to ethanol, methanol, propanol, butanol, acetone, ethyl acetate and dimethyl sulfoxide.

[0103] In an embodiment, in step (a), seaweed extract (suitably in powder form) is mixed with cold water or otherwise combined to form a paste. Any additives to be added, such as glycerol, may be suitably added at this stage. The paste is then heated (suitably mixed) to an elevated temperature. When heated, a seaweed extract hydrogel is formed. Suitably, the elevated temperature may be 80°C or higher, more suitably 80°C to 100°C, and even more suitably 90°C to 100°C. In an embodiment, the paste may be kept at the elevated temperature for between about 20 minutes and about 4 hours. Suitably, the contact is between about 1 hour and about 3 hours. Most suitably, the contact is about 2 hours.

[0104] In an embodiment, in step (a), the concentration of seaweed extract in the seaweed extract hydrogel can be 1% w / v to 10% w / v of the seaweed extract hydrogel, even more preferably 1% w / v to 8% w / v, more preferably 5% w / v to 6% w / v. In an embodiment, after step (a), additional water or other appropriate polar solvent is added to the hydrogel as appropriate to achieve the desired viscosity. Suitably, the consistency of the seaweed extract hydrogel used in step (b) is such that it is liquid. The total amount of water in the hydrogel can be between 100% and 300% of the original water volume added in step (a).

[0105] In an embodiment, in step (b), the concentration of the biodegradable filler in the mixture may be between 2 wt % and 10 wt %, more preferably between 4 wt % and 6 wt %.

[0106] In an embodiment, step (a) may be carried out at an elevated temperature. Suitably, the contacting may be carried out at a temperature greater than 80°C, more suitably in the range of 80°C to 100°C, even more suitably at a temperature of 90°C to 100°C.

[0107] In an embodiment, heating may be continued or restarted in step (b). During the mixing period in step (b), which in an embodiment is about 30 minutes, the mixture is heated to 90° C. After mixing is complete, the heat is removed and the mixture is allowed to cool.

[0108] When forming the seaweed extract hydrogel, foaming may occur due to the formation of bubbles in the mixture. During the entire heating process in step (b), foaming may continue. Foam can be removed at any time during or after step (b), and the formed foam can be removed repeatedly. Defoaming can be applied in steps (a) and / or (b). The degassing of the mixture can precede the removal of foam, or be carried out simultaneously. Degassing or other forms of removing bubbles from the solution can be carried out by themselves without removing foam. Such degassing can include stirring the mixture during heating to promote the release of bubbles from the mixture. Other forms of degassing, such as ultrasonic treatment and vibration at atmospheric pressure or under reduced pressure (vacuum), can be used alternatively or additionally and are also contemplated. Suitably, the mixture is degassed for about 2 hours to about 8 hours. Suitably, about 2 hours to about 6 hours. Most suitably, degassing is carried out for about 3 hours to about 4 hours. Suitably, degassing occurs while heating in steps (a) and / or (b) or immediately after heating.

[0109] At the end of step (b), the final concentrations of the components may be: seaweed extract in the range of between 1 wt% and 12 wt%, suitably between 5 wt% and 7 wt%; biodegradable filler in the range of between 3 wt% and 5 wt%; and water or other suitable polar solvent in the range of between 80 wt% and 90 wt%. All weight percentages are based on the total weight of the mixture at the end of step (b).

[0110] A mixture with a higher viscosity (before drying) produces (when dried) a denser, more structured product. If a mixture is prepared with a lower viscosity (before drying), the resulting (dried) product will generally be of lower density.

[0111] In an embodiment, the method may include the step of adding one or more additives as defined elsewhere herein in step (a) and / or (b). The additives may be dyes or pigments. These additives may color the composite material. Other additives may be salts or glycerol as described above. Suitably, salts or glycerol may be added to the mixture produced in step (a).

[0112] In another aspect, the present invention relates to a method for producing a product as defined above. The method comprises steps (a) to (c) as defined above for forming a composite material, and a step between steps (b) and (c) of forming or molding the mixture into the shape of a product.

[0113] The forming step may include molding. Suitably, molding may include casting, extrusion, compression molding, compression molding, injection molding, rotational molding or slide molding, blow molding. Most suitably, molding is compression molding.

[0114] The molding technique may be selected to be suitable for large scale manufacturing, such as injection molding, compression molding or casting.

[0115] The material is typically added to the mold at a temperature above ambient to maintain the desired fluidity of the mixture. Suitably, the material is added to the mold at about 80°C to 100°C or more suitably 85°C to 95°C. In embodiments, the material is added to the mold at about 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C. Suitably, the material is added to the mold at about 90°C. Below 70°C, the material may solidify, thereby complicating or preventing suitable molding.

[0116] When the liquid composite hydrogel containing biodegradable filler cools and solidifies (after an appropriate time), the mold can be separated and the material is left on at least one of the convex or concave parts of the mold, preferably on the convex part (or mandrel) of the mold, so that the solidified composite material is exposed to a dry environment, and thereby promotes the drying of the composite material by evaporating the solvent (suitably water) from the solidified gel. The drying process will generally continue until the composite material becomes suitably rigid and self-supporting (through the drying process) so that it can be demoulded to obtain a finished product. In some embodiments, the finished product has an appearance and characteristics comparable to PET plastics and PLA bioplastics. In addition, by retaining the solidified gel on the convex mold or mandrel during drying, shrinkage is controlled and deformation of the finished product is prevented.

[0117] In embodiments where the material is at least partially cooled in the mould, the composite material is cooled in the mould to ambient temperature. Suitably, the composite material may be cooled to a temperature below about 40°C and above about 0°C. Suitably, the composite material may be cooled to a temperature of about or exactly 30°C, 25°C, 20°C, 15°C, 10°C, 5°C.

[0118] In an embodiment, the composite material of the present invention can be dried at room temperature, pressure or infiltration. In an embodiment, the composite material can be dried in a controlled atmospheric environment (e.g., a low humidity environment or an environment in which the humidity is lower than that of the ambient atmosphere) or under reduced atmospheric pressure or under ultraviolet (UV) light. Composite materials can also be dried via osmosis in saline (salt and water bath solution), salt particles / powder or in corn or wheat flour / powder. Suitably, the device for drying composite materials can be carried out in a vacuum oven in which the boiling point of water decreases. The method is generally used for heat-sensitive materials, such as composite materials of the present invention.

[0119] In addition to or in place of other drying methods (including those described above), heating can also be applied to further promote drying, but care must be taken to avoid melting the composite material. In an embodiment, the composite material can be dried at a temperature below 60°C. Suitably, the composite material can be dried at a temperature between 30°C and 60°C, or between 30°C and 50°C, most suitably 40°C. Suitably, the composite material can be dried at a temperature of at least 30°C, 40°C or 50°C. Suitably, the composite material can be dried at a temperature of at most 60°C, 50°C, 40°C or 30°C. Compared to drying under ambient atmospheric conditions, in a drying environment (such as a vacuum oven) where atmospheric pressure is reduced, the required heating temperature can be reduced.

[0120] In other embodiments or in addition to those described above, the atmosphere above the mold containing the composite material during the drying step may have a low relative humidity. Suitably, the relative humidity of the atmosphere above the composite material may be about 70% or less. Suitably, the relative humidity of the atmosphere above the mold may be between 50% and 70%. Suitably, the relative humidity of the atmosphere above the mold may be about 60%, 55%, 50%, 45%, 40% or less.

[0121] In other embodiments or in addition to those described above, the atmosphere above the mold containing the composite material during the drying step can be at a pressure below the ambient atmospheric pressure. Suitably, during the drying step, the atmospheric pressure above the mold can be 7 psi to 14 psi. Suitably, the pressure is at most 14 psi, 13 psi, 12 psi, 11 psi, 10 psi, 9 psi, 8 psi, 7 psi or less. Suitably, the pressure is at least 1 psi, 2 psi, 3 psi, 4 psi, 5 psi, 6 psi, 7 psi or more.

[0122] Drying can be carried out, for example, at room temperature, in a dehumidifier (up to about 60° C.), and / or in a vacuum oven (up to about 60° C.).

[0123] In an embodiment, it is conceivable that the product can be reprocessed from a composite sheet with a suitable thickness. Reprocessing can include first forming a composite sheet of the present invention, such as by pouring or depositing the mixture derived from step (b) above onto a flat surface, and then cooling, and then drying the composite in a manner similar to that described above in the context of the die. In an embodiment, the sheet is fixed to a flat surface (suitably, by a suitable weight such as a plate) to prevent shrinkage or deformation during drying. The sheet formed by the composite can then be steamed and / or heated in the presence of water, such as by placing it in hot water (above 80° C.) for an appropriate length of time (e.g., 5 seconds), and then reprocessed into a desired shape. Suitably, reprocessing can be performed by wrapping the sheet and then keeping it in the contour of a suitable model. Once the composite has been sufficiently cooled and / or dried to form a product, the model can be removed. Vacuum forming can be used to reprocess the sheet by applying a vacuum to the sheet so that it is tightly pulled through a suitable model. For reprocessing, the sheet may have a suitable thickness (ie in its shortest dimension) prior to reprocessing of from 0.0.1 mm to 10 mm, more particularly from 1 mm to 5 mm, even more particularly from 0.5 mm to 1.5 mm.

[0124] In another aspect, the present invention also relates to a method of dissolving, degrading, biodegrading or otherwise safely breaking down the composite material or product of the earlier aspects of the invention described above. In addition to the material being able to rapidly and completely biodegrade (in less than 4 to 6 months) in a variety of natural and artificial environments (such as industrial composting facilities), the option of dissolving the composite material in water may be important in the management of waste streams.

[0125] In particular, the ability of the seaweed binder of the composite material to be readily soluble in water can be advantageous in helping to prevent the product / composite material from contaminating the plastic recycling waste stream (the composite material is intended for use in compost waste streams) when mistakenly discarded in a recycling bin by a consumer by facilitating its separation when the recyclable plastic is immersed in a liquid and washed prior to processing. In the composite material, only the seaweed component is soluble in water, while the biodegradable filler in the composite material, such as cork, is not soluble in water. Once the seaweed component is dissolved, the biodegradable filler (suitably cork) will be in granular form again and remain separate from the plastic and will not cause any damage during the plastic recycling process.

[0126] In an embodiment of the composite material or a product derived therefrom, the method of dissolving the composite material or product comprises the following steps: contacting the composite material or product with liquid water at a temperature of at least 50°C, more particularly at least 70°C, even more particularly at least 85°C. In this method, the composite material may comprise an amount of seaweed extract of 40% to 90% by weight, more particularly 60% to 600% by weight. In particular, the composite material may comprise an amount of biodegradable filler of 5% to 60% by weight, more particularly 30% to 50% by weight. More particularly, the composite material may comprise 1% to 20% by weight of water, even more particularly 2% to 15% by weight of water. Suitably, the composite material is contacted with water at a temperature of 90°C for 30 minutes to 1 hour under continuous stirring to achieve dissolution.

[0127] The composite material of the present invention or the product derived therefrom can be dissolved into harmless, food-safe water-soluble components, having the advantage of providing a simple and reliable waste disposal stream. This advantage is necessary if the composite material and / or product is to be completely and rapidly biodegraded in the environment. When disposed of by a properly managed waste stream, the above method provides a means for easy disposal of the composite material or product. The ability of the composite material to dissolve in water according to its temperature allows the selection of a specific composite material for a given use, depending on the environment, its expected time scale and the waste stream envisioned for that use.

[0128] Examples

[0129] Example 1 - Specific method for preparing thermal insulation composite material / composition according to the present invention

[0130] Kappa carrageenan (30 g) in powder form was added to 500 g of water (20° C.) and mixed for 5 minutes. In the embodiment where glycerol was added, it could be added at this stage. The resulting paste was placed in a hot water bath (90° C.) and warmed to 90° C. As the mixture temperature increased and reached 90° C., it became a liquid gel (hydrogel). The mixture was kept at 90° C. for 2 hours. Any foam collected was removed from the hydrogel mixture.

[0131] The biodegradable filler (24 g to 40 g) was then added to the hot kappa carrageenan gel and mixed for 30 minutes at a temperature of 90° C. Any foam that collected was removed from the biodegradable filler-hydrogel mixture.

[0132] The molded product is produced by pouring the prepared hot solution at 90°C into a female mold. The male mold is then pressed into the female mold (i.e., compression mold), and the solution is cooled to 25°C, whereupon the hydrogel solidifies. The mold is then separated, and the solidified biodegradable filler-gel attached to the male part of the mold is left to dry at 60°C under ambient pressure and humidity until it is completely dry (approximately 8 hours).

[0133] The obtained molded product contained the seaweed extract, water and filler in the proportions shown in Table 1 (contents by weight based on the total weight of the composition).

[0134] The relative weight percentages were calculated based on the water content determined by comparing the weight of the solidified gel before molding and the final weight of the product, assuming no loss of material mass of the biodegradable filler and kappa carrageenan during the preparation process, or no loss of water during the preparation before drying.

[0135] The resulting packaging is fully biodegradable and thermally insulating, and dissolves into a biodegradable filler in hot water at 80°C and above.

[0136] For the example of using cork as the biodegradable filler, the cork particles have an average particle size of 0.1 mm to 0.3 mm or 0.3 mm to 0.8 mm.

[0137] For the example of using sawdust as the biodegradable filler, the sawdust was obtained as waste from wood processing and had an average particle size of 0.5 mm.

[0138] For the example of using tea leaves as a biodegradable filler, tea leaves are obtained as waste from the beverage industry (having been brewed with boiling or near-boiling water, pressed, and then discarded). The pressed tea leaves are further dried to a moisture content of about 8 to 15 weight percent for storage to eliminate mold formation. The tea leaves have an average particle size of 0.5 mm.

[0139] For the example of using coffee grounds as a biodegradable filler, the coffee grounds are obtained as waste from the beverage industry (having been brewed with boiling or near-boiling water, pressed, filtered, and then discarded). The pressed coffee grounds are further dried to a moisture content of about 8% to 15% by weight for storage to eliminate mold formation. The coffee grounds have an average particle size of 0.5 mm.

[0140] For the example of using glycerol as an additive, it is indicated in the general experiment above that 30 grams of glycerol is added, and the resulting composition comprises 27% to 32% by weight of kappa carrageenan, 27% to 32% by weight of glycerol, 26% to 36% by weight of cork particles and 10% by weight of water (content by weight, based on the total weight of the composition).

[0141] Example 2 - Preparation of Exemplary Compositions

[0142] Compositions 1 to 7 according to the invention were prepared according to the general method of Example 1, replacing and / or adjusting the proportions of the seaweed product and the components as appropriate.

[0143] A comparative composition 8 not according to the invention was also prepared according to the general method of Example 1, from which the cork particles were omitted. A summary of compositions 1 to 8 is shown in Table 1:

[0144]

[0145]

[0146] Table 1

[0147] Example 3 - Thermal insulation

[0148] The ability of the embodiments of the compositions of the present invention to retard heat loss or transfer (thermal insulation test) was carried out using containers made from the compositions of the present invention comprising: different seaweed extracts; CK and agar and different biodegradable fillers and, for the embodiments using cork, cork particles of different sizes.

[0149] To measure the thermal insulation effect of the amount of biodegradable filler in the composition, the contents of seaweed extract and water were kept the same. On the other hand, the amount of biodegradable filler was increased by weight. The containers used were prepared using the general method of Example 1 and by forming each composition in the same mold (meaning that they were extruded to the same volume).

[0150] As a control, another composition (Composition 8) was prepared using only seaweed extract and water without adding cork particles to illustrate the thermal insulation effect of cork particles in the seaweed extract composition.

[0151] Ice cubes were placed in each test container at room temperature. After 10 minutes, the surface temperature of each container was measured from the outside using an infrared thermometer.

[0152] The results are shown in Table 2:

[0153]

[0154] Table 2

[0155] The results show that all compositions according to the invention (compositions 1 to 6) and 9 to 11 provide good thermal insulation capabilities. In general, cork appears to provide more outstanding results, and slightly better results appear to be obtained with larger cork particle sizes (compositions 1 to 3). In contrast, the seaweed-based composition in which no biodegradable filler was present showed the lowest thermal insulation capabilities (composition 8). Based on these results, the use of biodegradable fillers (and in particular cork particles) in seaweed-based compositions has clear advantages.

[0156] Example 4 - Moldability

[0157] The ability to mold the exemplary compositions of Example 2 was tested using the following method.

[0158] The compositions were formed in a compression mold comprising male and female parts. After removing a portion of the mold, the adhesive properties of each composition in the gel state were observed before drying. It was noted how the different compositions adhered to the mold to a lesser or greater extent.

[0159] During this demoulding process, the agar-based composition (Composition 7) was observed to break down. This indicates that the agar composition does not have sufficient tensile strength to withstand the demoulding process.

[0160] At the end of the drying process (right column below), the composition containing more than 40 wt% of cork particles with a size of 0.5 mm was observed to have cracked and damaged. On the other hand, when the cork particle size was reduced to 0.2 mm, up to 43% of cork particles could be used.

[0161] Good molding properties were observed for those compositions containing sawdust, tea leaves or coffee grounds.

[0162] The results are shown in Table 3 and Figures 1 to 8 middle:

[0163]

[0164] Table 3

[0165] Y = Qualitative positive results

[0166] N = Qualitative negative result

[0167] cork:

[0168] like Figure 1 As shown, Composition 1 was successfully dried on the mold without any cracks or fissures.

[0169] like Figure 2 As shown, composition 2 dried on the mold without any cracks or fissures. However, the material shrank and escaped from the mold, causing slight deformation.

[0170] like Figure 3 As shown, composition 3 developed cracks or fissures on the mold after drying. In addition, the material shrank and escaped from the mold, resulting in significant deformation.

[0171] like Figure 4 As shown, composition 4 had several cracks and fissures after drying on the mold. In addition, the material shrank and escaped from the mold, resulting in significant deformation.

[0172] like Figure 5 As shown, it was observed that the composition with smaller particles had a smoother and more uniform appearance on the surface.

[0173] Other biodegradable fillers:

[0174] like Figures 6 to 8 As shown, compositions 9 to 11 were dried on the mold without any cracks or cracks. Figure 8 After drying, remove from the mold and trim.

[0175] Example 5 - Density / Brightness

[0176] The density of the final dried composition was determined using compositions 1 to 7 and 9 to 11 of Example 2. As indicated by the mass of a given sample.

[0177] Each composition was poured into the same mold with the same volume. The final dry material weight and thickness were measured.

[0178] The results are shown in Table 4:

[0179]

[0180] Table 4

[0181] When the solid gels / compositions are initially demoulded (when wet), they all have the same thickness in the same mold. After they are left to dry on the male mold, the water evaporates and the material shrinks. Therefore, the final thickness after drying is determined by the water content and particle size of the biofiller. This also means that only the internal (hollow) volume is controlled by the male mold.

[0182] Density is measured by dividing the mass by the total volume (greater thickness means more total volume).

[0183] According to the results, the composition with the lowest density is composition 3, which has the highest cork content and the smallest cork particle size. Density is measured by dividing mass by volume (M / V); therefore, composition 3, which contains a particle size of 0.5, has the lowest density. However, since all compositions were molded to the same volume, composition 6, which contains a particle size of 0.2, is the lightest, but denser than the remaining compositions.

[0184] As can be seen from the table, the cork compositions (Examples 1 to 6) are lighter than the other tea leaves, sawdust and coffee grounds compositions (Examples 9 to 11).

[0185] Example 6 - Analysis of kappa carrageenan

[0186] The kappa carrageenan used in the above examples was identified as being derived from the tropical plant species Eucheuma cottonii / kappaphycus alvarezii (the two are often considered one in the industry), which was produced using a gel pressing process and without the addition of diluents.

[0187] An example of kappa carrageenan used in an exemplary embodiment of the present invention was analyzed. The overall comment is that the sample is a very common gel pressed kappa type with good color and excellent clarity. A general purpose grade, not a specific jelly, candy or dairy grade.

[0188] Typical properties and comments about the samples used are shown in Table 5:

[0189]

[0190] A very similar level seen in the past is Andi- AJK-491.

[0191] Table 5

[0192] Typical specifications of κ-type carrageenan used in the present invention are shown in Table 6:

[0193]

[0194] Table 6

[0195] Although specific embodiments of the present invention have been disclosed in detail herein, they are disclosed only by way of example and for the purpose of illustration only. The above embodiments are not intended to limit the scope of the present invention. The inventors contemplate that various substitutions, changes and modifications may be made to the present invention without departing from the scope of the present invention.

Claims

1. A composite material comprising a seaweed extract in an amount of 40 to 60 wt %, a biodegradable filler in an amount of 35 to 50 wt % and water in an amount of 2 to 10 wt %, based on the total weight of the composite material, in, The seaweed extract is carrageenan; and The biodegradable filler is selected from the group consisting of cork, tea leaves, coffee particles, sawdust, paper, hemp fiber, hay, straw, dry granulated food waste, dry granulated plant seeds, dry granulated fruit and vegetable peels or rinds, and mixtures thereof.

2. The composite material according to claim 1, wherein the composite material consists of the seaweed extract, the biodegradable filler and water. The composite material according to claim 1 , wherein the carrageenan is kappa carrageenan.

4. The composite material of claim 1, wherein the composite material does not contain one or more of the group consisting of: starch; iota carrageenan; agar; alginate; and chitosan.

5. The composite material according to any one of claims 1 to 4, wherein the biodegradable filler is cork. The composite material according to claim 1 , wherein the composite material further comprises one or more additives.

7. The composite material of claim 6, wherein the one or more additives are present in no greater than 20 weight % of the total weight of the composite material.

8. A composite material according to claim 6 or claim 7, wherein the one or more additives are selected from the group consisting of: salt and glycerol.

9. The composite material of claim 1, wherein the composite material is fully biodegradable.

10. The composite material according to claim 9, wherein the seaweed extract of the composite material: Completely biodegradable in less than six months in an external non-industrial environment; Completely biodegradable in an aerobic and / or anaerobic atmosphere; and / or Fully compostable in a home compost pile in less than six months It can be fully biodegraded in the ocean in less than 6 months.

11. The composite material of claim 1 , wherein the composite material is moldable.

12. A product formed from the composite material according to any one of claims 1 to 11.

13. The product of claim 12, wherein the product has a shape selected from the group consisting of: a plate; a planar sheet; a regular sphere; an irregular sphere; a regular sphere-shaped body; an irregular sphere-shaped body; a regular cube; an irregular cube; a regular cuboid; an irregular cuboid; a regular ellipsoid; an irregular ellipsoid; a regular cylinder; an irregular cylinder; a regular cone; an irregular cone; a regular prism; an irregular prism; a regular pyramid; an irregular pyramid; a shell-shaped, clam-shaped, or a shape having an internal void or hollow, and any combination thereof.

14. A method for producing a composite material according to any one of claims 1 to 11, the method comprising the following steps: contacting the seaweed extract with water to form a seaweed extract hydrogel, mixing the seaweed extract hydrogel with a biodegradable filler to form a mixture, and The mixture is dried to form the composite material.

15. The method of claim 14, wherein step a) comprises heating the mixture of the seaweed extract in water to a temperature in the range of 70°C to 100°C to form the seaweed extract hydrogel.

16. A method for producing a product according to claim 12, comprising steps a) to c) of the method for producing a composite material as claimed in claim 14 or claim 15, and the following additional step between steps b) and c): molding the mixture into the shape or three-dimensional form of the product.

17. A method of reprocessing a product, comprising producing the product by the method according to claim 16, wherein the method further comprises: f) softening or melting the product by contacting the product with water or steam to provide a softened product; g) further manipulating the softened product to provide a reworked product, wherein the reworked product has a different shape than the product; h) drying the reprocessed product to provide a dried reprocessed product.

18. A method for industrial biodegradation of a composite material according to any one of claims 1 to 11 or a product according to claim 12 or 13, the method comprising the following steps: The composite material or product is exposed to conditions in which the rate of biodegradation is increased.

19. A method of composting a composite material according to any one of claims 1 to 11 or a product according to claim 12 or claim 13, the method comprising the steps of: The composite material or product is exposed to conditions wherein the composite material or product degrades to form compost or a material suitable for use in compost or as a soil additive for use as a soil fertilizer.

Citation Information

Patent Citations

  • Composition adapted to be used for manufacturing stoppers and process of manufacture

    US5317047A

  • Closure for a product-retaining container

    WO2016020361A1

  • Edible composite film packing material with healthcare function

    CN104725671A

  • Process for producing high-swellability polymer composites

    CN105164171A